Analisis Kesalahan Mahasiswa Dalam Menyelesaikan Soal Persamaan dan Pertidaksamaan Pada Mata Kuliah Kalkulus I - Tuhfatul Janan (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
The goal of this research is to give description about the various errors that students make in solving equations and inequalities in the calculus I subject. The method in this research is qualitative and the subjects in this research were semester 1 students of Tadris Mathematics study program STAI Muhammadiyah Probolinggo. The techniques to collect the data were examinations and interviews. Based on the results of the study, it was concluded that there were 8 errors by the subjects in solving equations and inequalities in the calculus I course, namely errors in writing the equal sign , writing the conjunction or , equating the denominator of a linear equation, moving a number from one side to another in the equation linear, writing curly brackets , determining the situation of the numerator and denominator of fractions less than zero, writing down the interval sign and less than , and errors in writing the solution set.Keywords: Error Analysis, Equation, Inequality, Calculus